Answer:
≈ 634
Step-by-step explanation:
n = 847(1 * .07)^4
n = 847(0.93)^4
n = 633.60005247
n ≈ 634
Answer:
Assuming you want to simplify the expression, it can be shortened to:
-k² - 2k
Step-by-step explanation:
What you need to do here is called grouping like terms. Like terms can be described as terms that have the same factors. In this case, the factors we're looking at are k and k²:
Given:
k - 3k² -3k + 2k²
We'll rearrange to group like expressions:
= -3k² + 2k² + k -3k
Pull out common factors:
= (-3 + 2)k² + (1 - 3)k
And simplify:
= -k² - 2k
Answer:
285
Step-by-step explanation:
use algebra
third is x
second is 4x
first is 4x-3
x+4x+4x-3
9x-3 = x+x+1+x+2
9x-3=3x+3
12x=6, divide x=2
third is 2, sec is 8, first is 5
Answer: 25 percent of the jar is filled with orange candies
Step-by-step explanation:
In the jar, there are 3 yellow candies, 3 blue candies, and 2 orange candies. This means that the total number of candies inside the jar would be the sum of the yellow, blue and orange candies. It becomes
3 + 3 + 2 = 8 candies.
The percent of the jar filled with orange candies would be expressed as
number of orange candies/total number of candies × 100
It becomes
2/8 × 100 = 25%
Answer:
She will deposit $17.
Step-by-step explanation:
So this is really simple.
20% of $85= 0.20•85= 17=$17